Non-Glossolalic Charismatics: Psychological and Religious Characteristics and Their Interpretation - Meier, Augustine (Research in the social scientific study of religion, 1999)
Non-glossolalic charismatics were compared to two control groups on psychological and religious variables. Performance on psychological variables was assessed by the administration of Eysenck Personality Questionnaire (EPQ), Jackson’s Personality Research Form (PRF), Crumbaugh and Maholick’s Purpose In Life Test, the Allport-Vernon-Lindzey Study of Values (A-V-L), Schutz’s Fundamental Interpersonal Relations Orientation Questionnaire (FIRO-B), and Shostrom’s Personal Orientation Inventory (POI). Performance on religious variables was assessed using Hood’s Mysticism Scale Research Form D (MS) and Spilka’s Religious Orientation Scale (ROS). The data were analyzed using multivariate analysis of variance. Group differences were observed on PRF, MS, ROS, A-V-L, FIRO-B, and POI. The findings were interpreted with reference to strivings toward bonding and toward separating which, it is hypothesized, characterize the charismatic phenomenon.